Bridging the Islamic Banking Literacy Gap: The Role of Islamic Economics Education in Shaping Public Understanding of Islamic and Conventional Banking - Hasriadi; Zahru Ramadhan; Tarmizi Tahir; Ahmad Rijal Amiruddin; Ummul Wafiyah; Juhasdi Susono (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
This study discusses Islamic Economics Education in Improving Public Understanding of the Differences Between Conventional and Islamic Banks. The problems in this study are: (1) What is the level of public understanding regarding the differences between conventional banks and Islamic banks? (2) What forms of Islamic economics education can be used to improve public understanding of these differences? (3) How does Islamic economics education affect public understanding of the differences between conventional and Islamic banks?. This research is a qualitative study focused on document analysis. It employs educational, Islamic economic, and comparative approaches to analyze data obtained from literature or existing reference sources. These approaches aim to facilitate the comparison and evaluation of the collected data to gain a deeper understanding of the research subject. The research findings show that: (1) The level of public understanding regarding the differences between conventional and Islamic banks is still low. Therefore, this study suggests that Islamic economics education is a relevant solution as it significantly contributes to improving public understanding of the differences between the two banking systems. (2) Forms of Islamic economics education include Android-based applications, promotional education, YouTube education, mosque-based programs, lectures, and even educational games. (3) With Islamic economics education, public understanding—previously limited or nonexistent—improves regarding the distinctions between conventional and Islamic banks.